Clinical Case of Surreptitious Hypoglycemia Due to Deliberate Insulin Analog Administration. Issue 14 (April 2021) - Yukina, Marina; Nuralieva, Nurana; Troshina, Ekaterina; Malysheva, Natalya; Zuraeva, Zamira; Bratchikova, Alina
Hypoglycemic syndrome is a life-threatening condition that can lead to hypoglycemic coma and death. Surreptitious hypoglycemic syndrome is the deliberate use of insulin preparations or oral hypoglycemic drugs aimed to reduce blood glucose level. If human insulin is injected, high level of immunoreactive insulin (IRI) and low level of C-peptide at the moment of hypoglycemia are always detected. However, the fact of deliberate administration of insulin analogs is difficult to prove. In these cases if insulin kit test with low cross-reactivity with insulin analogs is used, the low levels of IRI and C-peptide will be suspected. Some experts suggest the presence of cross reactivity with analogs of insulin in a number of commercial kits, which makes it possible to detect cases of surreptitious hypoglycemia. We present a clinical case of a patient with surreptitious hypoglycemia due to the administration of insulin analogs and discuss the problems of its laboratory diagnosis.